2018
DOI: 10.1103/physrevlett.120.259901
|View full text |Cite
|
Sign up to set email alerts
|

Publisher’s Note: Biological Magnetometry: Torque on Superparamagnetic Beads in Magnetic Fields [Phys. Rev. Lett. 114 , 218301 (2015)]

Abstract: This corrects the article DOI: 10.1103/PhysRevLett.114.218301.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…106 For larger magnetic fields (10-100 mT), the angular thermal motion of surface-coupled particles was recorded to calibrate the magnetic torque. A quadratic scaling of the magnetic torque with field was found, 108 indicating that there is a net anisotropy in the MP, 103 or in other words, an easy-axis and a hard-axis. 104 A quadratic scaling of torque with field was also found for two-particle clusters of superparamagnetic particles.…”
Section: Magnetic Cores and Magnetic Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…106 For larger magnetic fields (10-100 mT), the angular thermal motion of surface-coupled particles was recorded to calibrate the magnetic torque. A quadratic scaling of the magnetic torque with field was found, 108 indicating that there is a net anisotropy in the MP, 103 or in other words, an easy-axis and a hard-axis. 104 A quadratic scaling of torque with field was also found for two-particle clusters of superparamagnetic particles.…”
Section: Magnetic Cores and Magnetic Particlesmentioning
confidence: 99%
“…However experiments have shown that a torque can be exerted on a single multicore superparamagnetic parti-cle. 106,108 The torque of single superparamagnetic particles with a diameter of 2.8 μm has been calibrated in small fields (<5 mT on Dynal M-280 particles 106 ) as well as in larger fields (10-100 mT on Dynal M-270 particles 108 ). For the small fields, the magnetic torque was calibrated based on the known hydrodynamic drag of a smooth sphere, which revealed a linear dependence of the torque on the applied field.…”
Section: Magnetic Cores and Magnetic Particlesmentioning
confidence: 99%
“…Many spherical paramagnetic particles also exhibit some magnetic anisotropy (Figure c) including in high‐quality commercial magnetic beads (e.g., Dynabeads, Themo Fisher Scientific, USA), coated spherical particles (e.g., Janus particles), and bioparticles (e.g., magnetotactic bacteria). The torque on these materials can be modeled in a similar fashion by obtaining the demagnetizing coefficients from experiment, simulation, or a theoretical solving of the magnetic energy of the system at each angle.…”
Section: Introductionmentioning
confidence: 99%
“…Since their synthesis, 1 stable suspensions of magnetic nanoparticles, such as ferrofluids, 2 have gained a lot of attention due to their broad potential in industrial [3][4][5] and medical applications. [6][7][8][9][10][11][12] Nowadays it is possible to functionalise the nanoparticle surfaces, 13,14 tune their shape [15][16][17][18][19][20][21] and control their internal crystalline structure. [22][23][24] Single-domain magnetic nanoparticles, having an intrinsic magnetic moment, effectively behave like nanomagnets.…”
Section: Introductionmentioning
confidence: 99%